Improving centre-based group exercise participation of older adults using the behaviour change wheel. Issue 1 (15th February 2021) - Kwok, Boon Chong; Wong, Wai Pong; Remedios, Louisa
Abstract : An emphasis on active ageing could help to delay the onset of frailty. In Singapore, Senior Activity Centres provide free and guided group exercise sessions for older adults. However, one such centre had very low participation rates among community-dwelling older adults despite running standardised programmes. Based on a needs analysis from a prior project, this paper reports on strategies implemented to improve the daily centre-based group exercise participation rate among community-dwelling older adults. Using the behaviour change wheel model, participant motivation domains were identified as primary gaps, while the psychological capability and physical opportunity were categorised as secondary gaps. A logic model was used to design a project to respond to these identified gaps and guide the evaluation approach. Three strategies were implemented over a 4-week period and reviewed at 6 months: (1) promotion of the exercise classes, (2) delayed rewards for participation and (3) health ambassadors. Evaluation findings highlighted that more resources were needed for the training of community-dwelling older adult healthcare ambassadors in the use of motivational interviewing. The interventions were found to be efficacious in increasing daily group exercise participation rate at the centre, from an average of three to nine participants per day over the 4 weeks. Furthermore, more than 60% of these participants achieved the WHO's weekly minimum exercise recommendation for older adults (150 min moderate-intensity physical activity). To increase the engagement of older adults in physical activity or exercise participation, we recommend the use of behaviour change wheel model and the use of community-based health ambassadors. In conclusion, the project found improved daily centre-based group physical exercise participation rates when all the domains in the behaviour change wheel model were addressed.